Women's Choice for Their Offspring: Checking on Investment in Human Capital - Apsari Anandari, I Gusti Agung Ayu; Husni, Vici Handalusia; Meisthya Pratiwi, Ida Ayu; Dyastari Saskara, Ida Ayu Gde (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
This study aims to examine the relationship between women’s time preference as a factor of her decision-making and children’s education within their household. We estimate the Multinomial Logit model using data from 2014 survey from IFLS-5. We use responses to hypothetical choice questions which has inter-temporal tradeoffs available on the survey data to determine individual time preference. Tentative results suggest that more patient women invested more in their children’s education. The children have better educational attainment and health condition due to the mother’s household decision. The proxy of individual time preference is attained only from hypothetical questions in which related to financial gain instead of educational and health gain. Other arguments that may arises is we assume that the time preference of one individual never changed during their lifetime. This study would help in designing education and health policy especially for children.